An analysis of electricity generation with renewable resources in Germany (2020)
Germany has an experience of renewable energy policies that encourages their usage, achieving technological migration and the redesign of its power generation matrix, achieving 112 GW of renewable resources at 2017. The research presents an analysis between the energy policies and the electricity statistics, the results forecast a date in which they will reach the goal of 50% of annual generation of total electric power by renewable sources, a goal set in 2012.